Should we draw, or should we work with numbers? Investigating proportional reasoning among 5th to 7th graders - Bereczki, Ildikó; Csíkos, Csaba (Teaching Mathematics and Computer Science, 2026)
Proportional reasoning is an essential component of our everyday life and our mathematics studies. The rate of development in this area varies between age groups. In order to find out the level of students in Grades 5–7, we developed an online test. We consider it important to emphasize and support the use of visual representations in this subject, and therefore the tasks of the test on the eDia (Csapó & Molnár, 2019) interface have three types of input and output.We distinguish between ratios represented visually in the form of discrete quantities, ratios represented visually in the form of continuous quantities and ratios represented by text or numbers. Our study aimed to explore the differences between task types. Results indicate a representation-dependent developmental shift: in Grades 5–6, students perform best on tasks involving visual discrete quantities, whereas in Grade 7, performance increases markedly on text-text tasks. This suggests that visual representations function as an early scaffold, while later instruction strengthens symbolic processing.Subject Classification: Primary: 97C30; Secondary: 97D40, 97D60